Epidemiology, pathogenesis, diagnosis and outcome of SARS-COV-2 cases in Uttar Pradesh: descriptive analysis - Singh, Amresh Kumar; Adhikari, Indra Prasad; Gaur, Vivek (International Journal of Research in Medical Sciences, 2021)
Corona virus is one of the major pathogens that primarily target the human respiratory system. Previous outbreaks of corona viruses include the severe acute respiratory syndrome (SARS)-CoV-2 and the Middle East respiratory syndrome (MERS)-CoV which have been previously characterized as agents that are a great public health threat. In late December 2019, a cluster of patients was admitted to hospitals with an initial diagnosis of pneumonia of an unknown etiology. These patients were epidemiologically linked to a sea food and wet animal wholesale market in Wuhan, Hubei Province, China. In India on 30th January 2020 first positive case in a student from Kerala of the SARS-CoV-2 infection, who was studying in Wuhan University and had travelled to India, tested positive by reverse transcriptase polymerase chain reaction (RT-PCR). As of 15th March 2021, in India total confirmed cases 94,61,901 recovery 88,47,600 death 1,37,582 have been reported from 32 states/union territories in U.P. state has 6,05,290 confirmed cases, resulting in 8,746 deaths and 595,637 recoveries. The case fatality rate in Uttar Pradesh was stands at 1.4%. Among different districts of U.P., the Lucknow was listed as first with 82,213 cases, 80,740 recovered and 1,190 deaths. Next states were Kanpur; 33,111 cases, and 839 deaths, Prayagraj 29,436 cases, and 409 deaths, Meerut; 22477 cases, and 442 deaths, Ghaziabad 26902 cases, 26694 recovered, 102 death and Gorakhpur 21510 confirmed case 21115 recovered and 366 deaths till 15th March 2021.